An Architectural Patterns Library to aid Systems of Systems Engineering. Issue 3 (October 2015) - Deiotte, Ray
ABSTRACT: Systems of Systems (SoS) are rapidly coming to dominate the engineering landscape. However, there are no structures or formalisms for their design, development, adoption, operation, and management. In other words, nearly every SoS Engineering (SoSE) project is a new work, building from the ground up, relying upon foundations built before, but not shared with the larger community. They remain unshared, not because of a lack of willingness, rather because there is no effective mechanism to share information on SoS without revealing proprietary information or trade secrets. In an effort to advance the science and art of SoSE and provide a mechanism for sharing information without infringing on propriety, we introduce the concept of SoS patterns, a SoS pattern library and propose to share it with the community. Rather than taking a purely theoretical view of SoS patterns (which is necessary), we provide a more pragmatic approach: building patterns from experience, providing helpful tools now while refining the generic, nominal patterns. We find that this approach provides not only an incremental, near‐term benefit, but also provides decision makers the information and evidence to assess risk and make informed decisions. In this paper, we describe a brief history of patterns, discuss their applicability and usefulness to the SoS problem, the components of a pattern and provide an example and vision for an open library of patterns for use by, and contribution from, the SoS community at large.